Platelet-Activating Factor Induces Epigenetic Modifications in Human Mast Cells - Damiani, Elisabetta (J Invest Dermatol, 2015)
Ultraviolet (UV) radiation-induced systemic immune suppression is a major risk factor for skin cancer induction. The migration of dermal mast cells from the skin to the draining lymph nodes plays a prominent role in activating systemic immune suppression. UV-induced keratinocyte-derived platelet-activating factor (PAF) activates mast cell migration, in part by up regulating the expression of CXCR4 on the surface of mast cells. Others have indicated that epigenetic mechanisms regulate CXCR4 expression, so we asked whether PAF activates epigenetic mechanisms in mast cells. Human mast cells were treated with PAF and the effect on DNA methylation and/or acetylation was measured. PAF suppressed the expression of DNA methyltransferase (DNMT) 1 and 3b. On the other hand, PAF increased p300 histone acetyltransferase expression, and the acetylation of histone H3, which coincided with a decreased expression of the histone deacetylase HDAC2. Chromatin immunoprecipitation assays indicated that PAF-treatment activated the acetylation of the CXCR4 promoter. Finally, inhibiting histone acetylation blocked p300 up-regulation and suppressed PAF-induced surface expression of CXCR4. Our findings suggest a novel molecular mechanism for PAF, activation of epigenetic modifications. We suggest that PAF may serve as an endogenous molecular mediator that links the environment (UV radiation) with the epigenome.